Effect of Heavy Metals on Different Anatomical Structures of Bruguiera sexangula - Gupta, Suparna; Chakrabarti, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The mangrove ecosystem is claimed to be the most productive ecosystem in the world when gross primary productivity and litter production is considered. In the study, an attempt has been made to generate information on the effect of three identified heavy metals viz., Hg, Pb and Cd, commonly found in the estuarine ecosystem, on Bruguiera sexangula by observing some important anatomical characters and heavy metal accumulation potentiality during their growth and development at ex situ. There was an increased tendency of hyper-accumulation of heavy metals with increased concentrations and time and the maximum accumulation was observed in the root area followed by stem and leaf. These findings suggest that the root acts as a barrier for metal translocation and protects the sensitive parts of the plants. The mode of heavy metal accumulation was observed to be in the order of Cd>Pb>Hg. From the anatomical study of root and stem, it was observed that the heavy metals at highest concentrations percolated into the hypodermal and stelar region. The stem anatomy of Bruguiera at 100 days after sowing (DAS) indicated deformed vascular bundle at treatment 1 and 4 of Hg. Xylem and phloem deformation was also recorded in treatment 1 and 4 of Cd which finally led to visible toxicity. Such detailed study indicated that the mangrove species Bruguiera can tolerate and accumulate the aforesaid three heavy metals (Hg, Pb and Cd) even at much higher concentrations. Hence, Bruguiera can be designated as hyper-accumulator. It may, therefore, be inferred that it could be effectively used for phyto-remediation purpose.